Comprehensive Review of Process Simulation to Industrial Applications and Sustainability Integration - Puspita Nurlilasari (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
Aspen HYSYS has become a foundational tool in process engineering, offering robust capabilities for modeling, simulating, and optimizing complex industrial processes. This review explores the application of Aspen HYSYS across diverse industries—including energy generation, petrochemicals, renewable fuels, and waste heat recovery—with a specific focus on heat and mass balance calculations. Through several validated case studies, we illustrate how HYSYS enables engineers to evaluate thermal efficiency, optimize mass flows, and reduce environmental impacts. The study includes detailed performance data for shell-and-tube heat exchangers, reactive distillation systems, organic Rankine cycles, and dehydration processes. Each simulation case is contextualized in terms of energy conservation and sustainable process design, demonstrating direct contributions to the United Nations Sustainable Development Goals (SDGs), especially SDG 7 (Affordable and Clean Energy), SDG 9 (Industry, Innovation and Infrastructure), and SDG 13 (Climate Action). Moreover, the review elaborates on numerical techniques and thermodynamic models used in HYSYS, offering guidance on choosing appropriate property packages and convergence settings. Challenges in fouling, turndown operation, and reference-state discrepancies in enthalpy tracking are also discussed. Ultimately, this article underscores the potential of process simulation not only as a tool for design and analysis but also as a driver of innovation and sustainability in industrial operations.